137k views
1 vote
3[x + (-2)] - 2x = -1

2 Answers

2 votes

Answer:

x=5

Explanation:

3(x-2)- 2x = -1

x-6= -1

x=5

User Max Shouman
by
5.0k points
0 votes

Answer:

x = 5

Explanation:

Given that:

3[x + (-2)] - 2x = -1 (constant multiplication)

3x + (-6) -2x = -1 (Multiplicating "+" sign with "-" we get "-")

3x -2x =-1+6 (Adding terms having same variables)

(As "-6" has now variable (x) so it will be transferred to other side to compute with like term "1" and its sign will be changed.)

x = 5 (Result)

User Miguev
by
4.6k points